Isotopic constraints on water balance and evapotranspiration partitioning in gauged watersheds across Canada - J.J. Gibson; T. Holmes; T.A. Stadnyk; S.J. Birks; P. Eby; A. Pietroniro (Journal of Hydrology: Regional Studies, 2021)
Study region: During 2013–2019, we conducted a Canada-wide program of streamflow sampling for the analysis of stable isotopic composition (18O/16O and 2H/1H), providing the first comprehensive survey for gauged watersheds across Canada ranging from 10 to 10,000 km2. A watershed-based assessment of vapour and runoff partitioning is presented for 103 watersheds across a diverse range of climate and land cover types, spanning 25° latitude and 86° longitude. Study focus: An isotope-based methodology is applied to estimate evaporation/inflow (E/I) and transpiration/evapotranspiration (T/ET) utilizing offset between isotope values in streamflow and precipitation, augmented by regional climate reanalysis data. Isotopic enrichment in streamflow serves to differentiate direct, abiotic evaporation, mainly arising from open water evaporation from lakes and wetlands, from transpiration by natural vegetation and cropland, which has previously been recognized as principally non-fractionating. Sensitivity analysis suggests only a minor influence of interception losses on T/ET. New hydrological insights for the region: Systematic variations in evaporation losses, transpiration losses and gauged runoff are revealed across the major hydrometric regions of Canada. Calculations suggest that E/I ranged from 2 to 60 %, while T/ET ranged from 25 to greater than 95 % across the watersheds. A new water loss classification is introduced which reveals that 19 of 103 watersheds were runoff-dominated, 54 were transpiration-dominated, 5 were evaporation-dominated, and 27 had more than one dominant water loss mechanism.